Implementation of “Positive Affirmation Therapy” in Depression Patients with Low Self Esteem Problems - Endriyani, Sri; Febriani, Indra; Pastari, Marta; Martini, Sri; Destrianah, Muthi’ah (Jurnal Multidisiplin Madani, 2023)
Low self-esteem can be caused by health problems, which are linked to poor interpersonal relationships and an increased risk of depression. Low self-esteem is accompanied by negative feelings which are the root cause of loss of self-confidence and represent weak self-esteem. The aim of this research is to find out how positive affirmation therapy is implemented to reduce levels of depression and improve low self-esteem. The type of research is descriptive in the form of a case study to explore the implementation of positive affirmation therapy in depressed patients with low self-esteem problems in the Ariodilah Public Health Center area of Palembang and the research subjects to be studied are 3 patients, namely depressed patients with low self-esteem problems. The results of the study showed that positive affirmation therapy in depressed patients with low self-esteem problems showed a decrease in depression levels and an increase in low self-esteem